The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles